(untitled) (Research, Society and Development, 2025)
Generational legacies passed down by great-grandparents are part of family memory and contribute to the family’s daily life. Great-grandparents are seen by children from the perspective of generativity and longevity, that is, as previous and founders of the family, as those who provide the notion of temporality, of the beginning and end of life. The aim of the present article was to analyze how great grandparenthood is portrayed in contemporary Brazilian children’s literature. To this end, twelve Brazilian children’s books were collected and analyzed, in which the theme of great-grandparents is portrayed. The results point to narratives that emphasize the issue of intergenerational transmission, bringing to light legacies in a material way, such as objects, and also as immaterial ones, which can be stories, advice and even feelings.